The people shapers - Packard, Vance Oakley, 1914- 4 0 16; 5 (New York : Bantam Books, 1977)
Examines current projects and developments in several scientific fields that are concerned with the physical modifications and behavior control of humans, including genetic engineering, bionics, and programming behavior.
Includes bibliographical references and index.
School Library Journal
Young Adult
Keywords: 2 -- 0; 6; Social aspects. -- Behavior modification.;Human genetics;Human engineering.;Eugenics.;Genetic engineering; 20; 2